The effects of augmented virtuality on presence, workload, and input performance - Clarkson, Jacob (Department of Computer Science, 2019)
Head-Mounted Displays (HMDs) offer, more than any easily accessible technology that has come before, the sensation of presence – that feeling that you are “really there” in a virtual world. However, HMDs cut the wearer off from the real world, making even trivial interactions, such as having a drink or typing, difficult and frustrating. In the home context where these devices are most likely to be used, such interactions are commonplace, and in order to execute them, users have to remove the HMD (“peep”), breaking their sense of presence. How, then, can real-world interactions during HMD usage be facilitated such that presence is damaged as little as possible? Previous work indicates that Augmented Virtuality (AV), a technique that allows the wearer of an HMD to see through it when they need to, is a promising answer to this question. However, direct comparisons between AV and VR that thoroughly account for presence and workload are lacking. To corroborate previous findings, and to address some of the gaps in the current literature, we conducted a quantitative user experiment to compare our own implementation of AV to VR in terms of presence, workload, and typing performance. The experiment followed a betweengroups design with participants selected via pseudo-random convenience sampling of university students. To simulate the context of home usage – an extended immersive session that must occasionally be interrupted – we designed a mixed reality game that periodically required the player to interact with real-world objects before they could proceed. Participants in the experimental group played the game using our AV system to assist them in completing the required real-world tasks. Participants in the control group used pure VR to play the game and had to peep. This allowed us to directly compare AV to VR in terms of the levels of presence and workload experienced. These data were gathered using post-hoc self-report questionnaires. To measure and compare typing performance under various conditions, we created desktop, VR, and AV versions of a typing test that participants had to complete. We found that typing performance in AV was significantly better than in VR, but did not reach the levels achieved in baseline desktop conditions. While there was not a significant difference in the overall level of workload associated with using AV compared to VR, participants in the AV condition were able to interact successfully with the real world without having to remove the HMD, and reported being significantly less frustrated than those in the VR condition. Finally, AV users reported significantly higher levels of presence than those who used VR.